Automotive electronics : proceedings of the Institution of Mechanical Engineers international conference - International Conference on Automotive Electronics (1994 : London); Institution of Mechanical Engineers (Great Britain). Automobile Division (London : Mechanical Engineering Publications, 1994)
20